14.4% efficiency all-polymer solar cell with broad absorption and low energy loss enabled by a novel polymer acceptor. (June 2020) - Jia, Tao; Zhang, Jiabin; Zhong, Wenkai; Liang, Yuanying; Zhang, Kai; Dong, Sheng; Ying, Lei; Liu, Feng; Wang, Xiaohui; Huang, Fei; Cao, Yong
Abstract: All-polymer solar cells (All-PSCs) offer several distinct merits including superior thermal stability and flexibility. Here, we report a novel polymer acceptor PJ1 that exhibits a narrow band gap around 1.4 eV and a high extinction coefficient about 1.39 × 10 5 cm −1 . When PJ1 is blended with donor polymer PBDB-T, all-PSC with a record power conversion efficiency (PCE) of 14.4% is achieved, which is mainly attributed to the broad absorption, efficient charge separation and collection, and low energy loss. The synergetic effects of molecular weight of PJ1 on the photovoltaic performance are also investigated. It is found that the increase in molecular weight can result in the red-shift of absorption along with slight enhancement of extinction coefficient, which therefore benefits photocurrent. In addition, all-PSC based on PJ1 demonstrate much better thermal stability than the control device based on small molecule acceptor (TTPBT-IC), as evidenced by the insignificant morphology change of PBDB-T:PJ1 versus excessive phase separation of PBDB-T:TTPBT-IC when annealed at 150 °C. Of particular interest is that the all-PSCs based on PBDB-T:PJ1 can retain high PCEs even when the thickness of photoactive layer is increased over 300 nm (PCE of 12.1%) or the device area is enlarged to 1 cm 2 (PCE of 13.0%). Graphical abstract: A novel polymer acceptor PJ1 that exhibits a narrow band gap around 1.4 eV and a high extinction coefficient about 1.39 × 10 5 cm −1 is synthesized. When PJ1 is blended with donor polymer PBDB-T, all-PSC with a power conversion efficiency of 14.4% is achieved, which is mainly attributed to the broad absorption, efficient charge separation and collection, and low energy loss. Image 1 Highlights: A novel polymer acceptor (PJ1) with narrow band gap (1.4 eV) and high extinction coefficient (1.39 × 10 5 cm −1 ) was designed. All-polymer solar cell with power conversion efficiency (PCE) of 14.4% was achieved by using PBDB-T:PJ1 as active layer. The devices derived from PJ1 exhibited stable morphology and high PCE retention rate upon thermal annealing. High PCEs of 12.1% or 13.0% were respectively obtained with an active layer thickness of 305 nm or a device area of 1 cm 2 .